IMPLEMENTING POLITENESS THAT CAN BE APPLIED TO THE FRONT OFFICE IN PROVIDING EXCELLENT SERVICE TO CONSUMERS - Melati Theresia; Yola Merina; Rani Autila (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
Front office is an important core in hotel, because the front office is the first to provide services to hotel visitors. Providing excellent service to consumers, front office should have know the foreign language. The language skill that should be  have by  front office is being able to speak politely to customers. The results obtained were (1) the front office got a theory about the importance of understanding cultural polite speech. (2) Increasing front office knowledge and understanding of polite speech when interacting with customer